Syntactic dominants in the poetic idiostyle of Mykhailo Kamenyuk - Pokhylyuk, Olenа (Current issues of Ukrainian linguistics: theory and practice, 2025)
This article explores the syntactic architecture of the poetic idiostyle of Mykhailo Kamenyuk through the lens of dominant syntactic patterns that characterize his lyrical discourse. Rather than treating syntax as a purely structural layer, the research repositions it as a dynamic stylistic and expressive resource central to constructing poetic meaning. The study identifies and categorizes recurring syntactic formations – such as ellipsis, inversion, rhetorical interrogation, fragmentation, and syntactic parallelism – as integral mechanisms by which the poet shapes the rhythm, imagery, and philosophical depth of his verse.Drawing upon Kamenyuk's 2020 poetry collection "...and the stone is ancient Latin, and the forest – Slavic script...", the article reveals how syntactic dominants perform beyond their grammatical functions, serving as semiotic vectors that articulate existential reflection, emotional density, and spiritual contemplation. These syntactic strategies, while linguistically rooted, function as compositional devices that support thematic cohesion and lyrical intensity.The analysis uncovers the poet's deliberate deviation from conventional syntactic templates in favor of expressive discontinuities, creating fragmented yet symbolically charged utterances. Inversions disrupt expected word orders to produce semantic reorientation and emphasis, while ellipses introduce ambiguity and introspective depth. Rhetorical questions, frequently used without anticipation of an answer, emerge as dialogic tools that establish a confessional tone and meditative atmosphere. Meanwhile, graphic and prosodic segmentation of syntactic units reflects a poetics of pause and pacing, whereby the visual arrangement of lines mirrors emotional cadence and internal conflict.Moreover, the article emphasizes the synergy between syntactic construction and poetic scenography: the alignment of phrase-level structures with visual layout intensifies the expressive modality of the poetic voice. This interplay positions syntax not only as a linguistic phenomenon but as an aesthetic framework that encodes the poet's worldview. Kamenyuk's idiostyle thus emerges as a synthesis of grammatical experimentation and metaphysical inquiry, where syntactic dominants anchor the lyrical subject's navigation through spiritual, ethical, and emotional landscapes.The study contributes to broader idiostylistic scholarship by highlighting the value of syntactic analysis in poetic stylistics. It advocates for an integrated approach that considers syntax as a key site of authorial intention and poetic innovation. Future research may benefit from comparative perspectives involving other contemporary Ukrainian poets or cross-level stylistic correlations, particularly those linking syntax with phonetic or lexical features. Overall, the article affirms the significance of syntactic dominants in manifesting the linguistic uniqueness of Kamenyuk's poetic world.
Keywords: poetic idiostyle; syntactic dominants; inversion; ellipsis; rhetorical question; parcelling; Mykhailo Kamenyuk